Impedance measurement for advanced battery management systems - Howey,DA; Yufit,V; Mitcheson,PD; Offer,GJ; Brandon,NP (2014)
We present a fast, low-cost approach to measure battery impedance 'on-line' in a vehicle across a range of frequencies (1-2000 Hz). Impedance measurement has promise for improving battery management since it is a very effective non-invasive method of diagnosing the internal state of an electrochemical cell. It is useful for estimating temperature, ageing, state of charge (SOC) and for fault detection. The aim of this paper is firstly to explore the usefulness of impedance for estimating SOC, focusing on lithium-ion iron phosphate (LFP) and nickel manganese cobalt oxide (NMC) cells, and secondly to demonstrate the performance of a low cost impedance measurement system that uses an existing motor drive similar to that of an electric vehicle to excite the battery current. We find that measurements made with this system are accurate to within a few per cent of results from an expensive, bulky commercial system. For SOC estimation in NMC cells, the charge transfer resistance and SEI layer resistance vary significantly with SOC. In LFP cells the parameter variation is much less obvious, although the double layer capacitance of the full pack may be a useful indicator of SOC.